Robust PID Control Design in CPS-based Batch Distillation Column - Wirenda Sekar Ayu; Pranoto Hidaya Rusmin; Egi M. I. Hidayat (IAES Indonesia Section, 2019)
Interconnected system between computationand physical process (Cyber-Physical Systems) has been widelyused in industrial processes. In CPS-based industrial process,sensors, controllers, and actuators are connected into acommunication network. The communication network mayintroduce delay time uncertainties due to shared resources andload traffic in the network. Furthermore, the nonlinear timevaryingcharacteristic of batch distillation column may causesanother uncertainties to take into account in control systemdesign. Parameter model and delay process uncertainty isintroduced due to linearized system approximation thatunmodeled high-frequency dynamics. The dynamicuncertainty on both I/O channel are also introduced to thesystem uncertainty. In this paper, robust PI and PID controllerusing AMIGO method with appropriate weighting function isdesigned to guarantee robust stability spesification of batchdistillation column. The impact of system uncertainties toclosed-loop system performances such as peak overshoot andintegral error is investigated. MATLAB/Simulink simulationis used to validate the methods before its implementation inCPS-based batch distillation column. Based on simulation, theproposed robust PI/PID controller can guarantee robuststability of system compared to conventional PID controller.Furthermore, the robust PI/PID controller can improve closedloopsystem performances compared to conventional PID.